Aplikasi Toko Online Berbasis Web Studi Kasus Pada Cilla Shop - Pitri; M. Syafiuddin Usman (SATESI: Jurnal Sains Teknologi dan Sistem Informasi, 2023)
Cilla shop stores that are engaged in sales, promotions and technology as well as waiters that make it easier for customers to make transactions can be a supporting factor in achieving sales success. In order to facilitate it all can be realized with an online store (E-Commerce). The built online store application aims to help the "Cilla Shop" store in terms of product marketing and sales. The process of making this program begins by analyzing the existing system in the store, then creating UML (Unified Modeling Language) and the necessary tables followed by designing the interface and making the program. This online shop application uses the programming language PHP, MySQL as a database, Sublime Text as an HTML editor. This application has three main functions. First, for customers/general users, each website visitor can view the product catalog, use website services, but cannot place product orders. The second is members who can order products. Finally, the administrator can manage product data, manage orders and obtain reports.